Barang Milik Negara: Kebebasan Berkontrak Pada Perjanjian Pemerintah - Kevin Bhaskara Sibarani (PROGRESIF: Jurnal Hukum, 2022)
State Owned Asset (SOA) utilization is a part of the management of state assets as an alternative in providing income for the state through non-tax state revenue. The implementation of the utilization of SOA is stated in the form of an agreement or contract between the government and the partner which can come from the private sector. This research will analyze the provisions or arrangements of the SOA utilization agreement related to the contract law in Indonesia and the application of freedom of contract in the SOA utilization contracts. The results of this reseatch indicate that the principle of freedom of contract is not absolute and the application of freedom of contract in the SOA utilization agreement is limited by the laws and regulations governing the provisions in the management of SOA. This research was conducted using a normative juridical method through a conceptual approach and a statutory approach. The SOA utilization agreement practically is an implementation of statutory regulations, however, the application of freedom of contract in its application can be seen from the stages of the contract, i.e. the pre-contractual, contractual and post-contractual stages in determining the contents and provisions of the agreement as long as it does not conflict with the provisions of the legislation, decency and public order.